Feasibility of Collecting Biologic Specimens in Population-based Surveys: Experiences from the Epidemiology of Hepatitis C in the Household, Adult Population of Puerto Rico Study - Pérez, Cynthia M.; Marrero, Edmir; Meléndez, Marytere; Adrovet, Sandra; Colón, Héctor; Albizu, Carmen; Torres, Esther A.; Ortiz, Ana P.; Suárez, Erick (Puerto Rico Health Sciences Journal, 2010)
The Behavioral Risk Factor Surveillance System (BRFSS) collects data on preventive health practices and risk behaviors that are linked to chronic diseases, injuries, and preventable infectious diseases that affect the adult population in all states and territories in the US . The BRFSS is currently the only survey conducted annually in Puerto Rico in the population aged 18 years and older; however, prevalence estimates are based on self reports and therefore are subject to reporting errors. Although surveillance data are useful for the purpose of evaluation, program planning and health policy, surveys that collect biological specimens and clinical data provide a more accurate assessment of prevalence and a comprehensive picture of disease distribution and their risk factors. This article summarizes the methodology employed in a population-based study to estimate the seroprevalence of hepatitis C and other viral infections in Puerto Rico and shows the feasibility of combining different modes of data collection in population-based surveys that collect biologic specimens. [P R Health Sci J 2010;1:18-25]